2004
DOI: 10.1001/jama.291.4.476
|View full text |Cite
|
Sign up to set email alerts
|

How Do Institutional Review Boards Apply the Federal Risk and Benefit Standards for Pediatric Research?

Abstract: EDIATRICIANS OFTEN MUSTtreat children in the absence of sufficient data. 1 For example, approximately 70% of all medications do not include sufficient data for use in children. 2,3 To provide the necessary data and to ensure medical interventions are safe and effective for children, it is necessary to conduct clinical research with children. 4,5 Currently, more than 1900 clinical trials are approved for children in the United States. 6 Food and Drug Administration (FDA) requests have led to proposals to enroll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
157
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(161 citation statements)
references
References 9 publications
3
157
0
1
Order By: Relevance
“…For all these reasons, proposed research may or may not proceed on the basis of what might be considered subjective determinations of minimal risk by REBs. The literature clearly substantiates difficulties with the use of a nebulous standard for minimal risk and although other standards have been proposed for use, they have yet to be adopted 35,36,37,38,39,40,41,42,43,44 .…”
Section: Concerns To Consider When Rebs Review Research Proposals Invmentioning
confidence: 99%
“…For all these reasons, proposed research may or may not proceed on the basis of what might be considered subjective determinations of minimal risk by REBs. The literature clearly substantiates difficulties with the use of a nebulous standard for minimal risk and although other standards have been proposed for use, they have yet to be adopted 35,36,37,38,39,40,41,42,43,44 .…”
Section: Concerns To Consider When Rebs Review Research Proposals Invmentioning
confidence: 99%
“…36 My approach is to determine the level of risk associated with both treatment arms, ascertain whether the potential risks associated with the 2 treatment arms are identical (unlikely) or different, and then confirm that the risks and benefits are equivalent to those of care outside of the research.…”
Section: Are the Risks Of The Research Reasonable In Relation To The mentioning
confidence: 99%
“…In addition, the risks of routine clinical examinations and daily life activities are dissimilar to net research risks because people mostly incur them for their own benefit rather than for the benefit of others. For these reasons, the minimal risk threshold, although widely endorsed, has been notoriously difficult to define and implement (Shah et al 2004;Lenk et al 2004).…”
Section: Step 7: Evaluate Whether the Remaining Net Risks Are Justifimentioning
confidence: 99%
“…Indeed, empirical studies have found significant variation in how IRBs/RECs evaluate research risks and potential benefits (van Luijn et al 2006;Shah et al 2004;Lenk et al 2004). These data raise concern that some participants are not being protected from excessive risks and that valuable studies involving acceptable risk are being rejected-or not even submitted given the uncertain outcomes of ethical review.…”
mentioning
confidence: 99%